UNHCR in Uganda: better than its reputation suggests - Jones, W (Refugee Studies Centre, University of Oxford, 2013)
Mistrust and fear abound among Rwandan refugees in Uganda. The dearth of information available about Cessation urgently needs to be addressed by UNHCR